Pelatihan Songket Pita untuk Meningkatkan Kreativitas Santri di Islamic Boarding School - Ospa Pea Yuanita Meishanti; Siti Saudah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
Students at the Al-Fatich Islamic Boarding School, Bahrul Ulum, Jombang Rice Pond Student. Experiencing many obstacles / obstacles in minimizing used clothes. The used clothes are increasing every year and the students who have returned (boyong) leave some of the clothes they don't wear. With the use of used clothes will help reduce and become useful items (upcycle). This effort leads to the goal of using used clothes to get an overview of the three upcycle techniques from the point of view of design, the process of designing, and creating, the use of used fabrics, and the overall results. The results of the santri skills assessment show that 60% of the training participants have good skills when the students learn to make ribbon embroidery patterns. As many as 40% of the training participants were in the category with fairly good skills which was influenced by the age of the students around 18-23 years.